Turboroundabouts along corridors analysis of operational and environmental impacts - Fernandes, Paulo (2018)
The number of turbo-roundabouts constructed in Europe has grown steadily in the past decade. While there has been extensive work on the operational and environmental impacts of isolated turbo-roundabouts, research on closely-spaced turbo-roundabouts along corridors is somewhat lacking. The objective of this research is to evaluate the impact of turbo-roundabout corridors on both traffic performance and emissions. The research has three major thrusts: 1) to identify the hotspot emission locations along turbo-roundabout corridors; 2) to compare the overall performance of turbo-roundabout corridors against conventional two-lane roundabouts on arterials; 3) to address the integrated effect of geometric and operational characteristics of turbo-roundabout corridors on carbon dioxide, carbon monoxide, nitrogen oxides and hydrocarbons emissions. Vehicle activity along with traffic flow data were collected from three turbo-roundabout corridors in the Netherlands. Site-specific operations were analyzed using microscopic traffic and emissions platforms (respectively, VISSIM and Vehicle Specific Power – VSP). The results showed that emission hotspots along these corridors occurred in the segments located just downstream of the turbo-roundabout, both in absolute terms (more than 30% of total emissions) and per unit distance. It was also found that the implementation of two-lane roundabout corridors outperformed the turbo-roundabout corridors in terms of vehicle emissions, however the differences were not statistically significant (p-value<0.05). Data analysis indicated that an additional decrease in corridor’s emissions (4-11%, depending on the pollutant) may be reached by altering the spacing (from 180 to 240 m) between two-closely spaced turbo-roundabouts.